Review of Jennifer Milioto Matsue. 2009. Making Music in Japan’s Underground: The Tokyo Hardcore Scene. New York and London: Routledge - Sollee, Kristen (Current Musicology, 2011)
Jennifer Milioto Matsue’s ethnographic account of Tokyo hardcore in the late 1990s situates the scene both within the context ofJapanese society and underground music scenes in urban centers around the world. The author characterizes this enclave of hardcore music making as both distinctively Japanese and simultaneously comparable to other music scenes outside Japan. Matsue’s research spans from 1996 to 1999 and revolves around the band Jug and the club or “livehouse” they frequent, 20,000volt. Other bands and participants on the periphery of this particular group are discussed, although the ethnographer is most intimately involved with Jug, and eventually joins them during a few live performances as a guest vocalist. Crucial to Matsue’s narrative is a concept of performance that includes both acts onstage and (inter)personal contributions within the scene. Making Music in Japan’s Underground: The Tokyo Hardcore Scene is divided into four chapters that progressively delve into the tightly-knit world of Tokyo hardcore. The first chapter gives context for the ethnography, providing an overview of Tokyo at the end of the century and establishing the dominant traits of American and Japanese hardcore music. While not attempting the dubious task of defining a genre, Matsue begins by outlining the basics of American hardcore, briefly touching on the genre’s birth out of the punk rock movement, and its subsequent connection to both grunge and alternative rock in the 1990s. Taking punk tempos and speeding them up, hardcore is described by the All Music Guide (cited by Matsue) as incorporating guitars with a “monochrome” timbre and “half-shouted lyrics venting the most inflammatory sentiments the singers and songwriters could devise”. Leftist politics are central to the early strain of hardcore in the United States and, as Matsue writes, citing Roy Shuker, the music created in the hardcore scene was “initially distinct from mainstream production systems”.While Matsue fails to explain how and when hardcore made its way to Japan, her cursory overview of American hardcore allows her to compare and contrast the Japanese scene with its Western antecedent. Stylistically, the hardcore scene in Japan that she analyzes is “a range of musics loosely connected under the umbrella style of hard core … [incorporating] a guitar rock or kitschy punk aesthetic, with quite a lot of screaming … or intensive mumbling”. Although independent modes of musical production remain important, radical politics are far less prevalent, and the performative aggression is more about momentary release than attempting to effect permanent political or social change. Matsue writes, “Performance in the scene allows participants a space to negotiate distinct individual and collective identities that can at times be further characterized by a sense of resistance, but this resistance is often temporary, even playful”. This description is in keeping with Matsue’s understanding of play. In her usage, play denotes a temporary leisure activity outside of work. Play also encompasses her definition of performance, which is specifically the creation of music onstage and the methods of production and distribution offstage (such as creating promotional flyers or starting independent record labels) that perpetuate the scene and facilitate live performances. Play can also include shifting aspects of one’s identity and persona that may result in resistance against conventional societal roles, although in a fashion that is not permanent.